An approach in integrating safety and usability into an automotive navigation interface - Syed Mohamed, Muhammad Syafiq (2017)
Automotive navigation interface designs have the potential to cause distractions to drivers. The National Highway Traffic Safety Administration (NHTSA) crash data showed that 17 percent (an estimated 899,000) of all police-reported crashes involved some type of driver distraction in year 2010. Of those 899,000 crashes, distraction caused by instrumentations residing in the vehicle was reported in 26,000 crashes. It is important to address the issue of safety and usability in multimedia and navigation systems, in order to reduce the problem of driver’s distraction. Common usability problems with automotive navigation user interfaces are legibility, cluttered interfaces, and the map design in general. This study contains three major components, namely to ascertain the automotive navigation user interface design elements, to integrate the needs of Malaysian drivers into the automotive navigation interface design and lastly to evaluate the proposed automotive navigation interface design for Malaysian drivers. Relevant design elements for an automotive navigation interface were studied using content analysis of an online Malaysian GPS forum. As many as 235 comments were analyzed. Following the conclusion of the content analysis method, the Kansei Engineering approach was utilized to integrate safety and usability in an automotive interface design, after which a new prototype of an automotive navigation interface was developed. A usability testing was conducted to evaluate the new automotive navigation interface prototype. Results from the content analysis showed that several important design elements were noted such as “Points of Interest”, “3D Buildings”, “Maps” as well as “Driving Safety”. In the second phase of the study, the Kansei Engineering results were analyzed with Principal Components Analysis (PCA) as well as Partial Least Squares (PLS) method. Equations relating Kansei words of safety and usability were obtained. A finalized list of design specifications was developed and the design specifications were then used to develop a new automotive navigation interface design, in the form of an animated prototype. During the usability testing, a Wilcoxon signed-rank test showed that the newly proposed automotive navigation interface design performed better than the existing automotive navigation interface design in terms of the Kansei usability survey (Z=-2.386, P=0.017), number of driving errors (Z=-4.989, P <0.00), and task completion times (Z=-3.015, P=0.003) whereas the System Usability Scale (SUS) scores showed no significant difference (Z=-0.990, P=0.322), although the SUS score for the new automotive navigation interface design was slightly higher (66.625) compared to the existing automotive navigation interface design (62.625). As a conclusion, the Kansei Engineering approach worked very well in integrating the safety and usability requirements for an automotive navigation interface design.